The Effectiveness of Utilizing the Film Encanto in Increasing Students' Vocabulary - Chintia Brevieta Sako; Moon Hidayati Otoluwa; Magvirah El Walidayni Kau (Research Review: Jurnal Ilmiah Multidisiplin, 2023)
The purpose of this research is to find out the improvement of students’ vocabulary after using film encanto. The population of this research is the students in ten grade of SMAN 4 Gorontalo, and the sampel is 24 students in class X MIPA 4. This research used pre-experimental design with one group pre-test, treatment and post-test. The result of this research shows that the mean score of pre-test is 9,04 and the mean score of post-test is 12. Moreover, the result of hypothesis of this research found that tcount tlist or 6,040 2,074. It means that the hypothesis (H1) of this research is accepted, there is 40,49% score results resceived from the pre-test to the post-test. Therefore, it can be concluded that the utilizing the film Encanto increase Students’ Vocabulary. Keywords :Film Encanto, increasing students’ vocabulary